Bayesian Islamic medication expert system (B-IMES) - Daud, Hanita; Razali, Radzuan; Jung, Low Tan; Zaida, Shahnaz (2015)
This paper discusses on the development of an expert system (ES) that applies Bayesian Probability concept for Islamic Medication practice that is made available on web platform. This ES allows user to choose sickness such as headache, stomachache, toothache and etc that he/she may have and list of symptoms related to the sickness will appear for the user to choose. Once symptom(s) is/are chosen the diagnosis is being carried out to suggest percentage of possible specific sickness such as classic migraine, common migraine, tension headache and etc if headache was chosen. This diagnosis is being carried out using Bayes’ Theorem and the ES will suggest the treatments or therapy that he/she needs to perform in reference to Muslim Holy Quran and Hadith. This ES was developed to preserve Islamic medication and to create awareness among the young generation and make it accessible at anytime and anywhere and to save users time to meet Islamic Medication practitioners who are not easily available in Malaysia and other parts of the world.